2016
DOI: 10.4322/rbcv.2016.032
|View full text |Cite
|
Sign up to set email alerts
|

Hipomagnesemia subclínica em vacas leiteiras durante o período de transição: ocorrências hormonais e metabólicas

Abstract: O objetivo, com este estudo, foi investigar as conseqüências da hipomagnesemia subclínica sobre parâmetros metabólicos de vacas leiteiras. Amostras de sangue foram coletadas de 12 animais, a cada dois dias, entre os dias 22 pré e 22 pós-parto, para a realização de análises sanguíneas e determinação do perfil metabólico. Os animais foram categorizados de acordo com os níveis séricos de magnésio: Grupo Hipomagnesêmicas (n=5), com níveis abaixo de 1,8 mg/dL em ao menos dois dias consecutivos, e o Grupo Controle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a study carried out by Alvarenga et al (2015), of the 12 animals evaluated, one presented subclinical hypomagnesemia (1.67 mg.dL -1 ) five days after calving. Schimitt et al (2016), evaluating 11 cows during the transitional period, found that five presented subclinical hypomagnesemia (blood levels below 1.8 mg.dL -1 ) in both pre-and postpartum episodes, with emphasis on two cows whose Mg concentrations remained below normal serum levels for 60% of the experimental period. For the peripartum cow, the status of the Mg interferes with Ca metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study carried out by Alvarenga et al (2015), of the 12 animals evaluated, one presented subclinical hypomagnesemia (1.67 mg.dL -1 ) five days after calving. Schimitt et al (2016), evaluating 11 cows during the transitional period, found that five presented subclinical hypomagnesemia (blood levels below 1.8 mg.dL -1 ) in both pre-and postpartum episodes, with emphasis on two cows whose Mg concentrations remained below normal serum levels for 60% of the experimental period. For the peripartum cow, the status of the Mg interferes with Ca metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lean et al (2006), an increase in Mg concentration of 3 to 4 g.kg -1 dry matter in the animals' diet can reduce the risk of hypocalcemia in the herds by approximately 62%. Of the cows evaluated by Schimitt et al (2016), 41% presented subclinical hypomagnesemia, with the animals under continuous grazing of Brachiaria Decumbens and receiving commercial mineral supplement at will. The data is similar to that found in this study, where the group of cows that received commercial mineral supplement had the lowest levels of Mg in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations